Temporal Interactions Among Carnivores in an Anthropized Landscape of the Coastal Mountain Range in Southern Chile - Zuñiga-Alvarez, A (Institute of Forest Ecology of the Slovak Academy of Sciences, 2025)
The structuring of carnivore assemblages is based on the partitioning of niche axes, where the activity pattern is relevant for their coexistence. However, the continuous degradation of habitats, and the human presence (and exotic species) limit the availability of resources. Therefore, these species must readjust their requirements to minimize interactions derived from competition. For two years, activity patterns of two native carnivores (the cougar Puma concolor and the chilla fox Lycalopex griseus), one exotic carnivore (the domestic dog Canis lupus familiaris) and people were evaluated in an anthropogenic landscape in southern Chile. A differentiation was observed in the circadian cycle of the species, where the fox was predominantly nocturnal, while the cougar maintained a random activity pattern, in contrast to the dog and humans, which were the most diurnal. The ecological implications derived from the observed patterns are discussed, mainly in relation to the interference exerted by the exotic species. © 2024 Authors.